Effect of hepatic cytochrome P450 (P450) oxidoreductase deficiency on 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine-DNA adduct formation in P450 reductase conditional null mice - Arlt, Volker M.; Singh, Rajinder; Stiborová, Marie; Costa, Gonçalo Gamboa da; Frei, Eva; Evans, James D.; Farmer, Peter B.; Wolf, C. Roland; Henderson, Colin J.; Phillips, David H. (Drug metabolism and disposition, 2011)
2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), formed during the cooking of foods, induces colon cancer in rodents. PhIP is metabolically activated by cytochromes P450 (P450s). To evaluate the role of hepatic P450s in the bioactivation of PhIP, we used Reductase Conditional Null (RCN) mice, in which cytochrome P450 oxidoreductase (POR), the unique electron donor to P450s, can be specifically deleted in hepatocytes by pretreatment with 3-methylcholanthrene (3-MC), resulting in the loss of essentially all hepatic P450 function. RCN mice were treated orally with 50 mg/kg b.wt. PhIP daily for 5 days, with and without 3-MC pretreatment. PhIP-DNA adducts (i.e., N-(deoxyguanosin-8-yl)-2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine [dG-C8-PhIP]), measured by liquid chromatography-tandem mass spectrometry, were highest in colon (1362 adducts/108 deoxynucleosides), whereas adduct levels in liver were ∼3.5-fold lower. Whereas no differences in PhIP-DNA adduct levels were found in livers with active POR versus inactivated POR, adduct levels were on average ∼2-fold lower in extrahepatic tissues of mice lacking hepatic POR. Hepatic microsomes from RCN mice with or without 3-MC pretreatment were also incubated with PhIP and DNA in vitro. PhIP-DNA adduct formation was ∼8-fold lower with hepatic microsomes from POR-inactivated mice than with those with active POR. Most of the hepatic microsomal activation of PhIP in vitro was attributable to CYP1A. Our results show that PhIP-DNA adduct formation in colon involves hepatic N-oxidation, circulation of activated metabolites via the bloodstream to extrahepatic tissues, and further activation, resulting in the formation of dG-C8-PhIP. Besides hepatic P450s, PhIP may be metabolically activated mainly by a non-P450 pathway in liver.